Pengaruh Pelapisan Kitosan dan Perlakuan Pengemasan Terhadap Masa Simpan Brokoli (Brassica oleracea var. Italica): Pengaruh Pelapisan Kitosan dan Perlakuan Pengemasan Terhadap Masa Simpan Brokoli (Brassica oleracea var. Italica) - Niken Ayu Setyaputri; Theresa Dwi Kurnia (Universitas Bangka Belitung, 2019)
The main purpose of this study was to analyze the effect of chitosan concentration as a natural coating material combined with packaging treatment on broccoli. The other purpose was to extend the shelf life and quality of broccoli during storage at low temperatures, by determining the appropriate concentration of chitosan during storage at low temperatures (5°C). The experimental design used in this study was a factorial completely randomized design. The treatment factor for chitosan concentration was control (0%), 0.5%, 1%, and 2%, combined with plastic wrapping and without packaging treatment. Combination of treatments: (1) not coated with chitosan (0%) without packaging treatment, (2) concentration of 0.5% chitosan without packaging treatment, (3) 1% chitosan concentration without packaging treatment, (4 ) 2% chitosan concentration without packaging treatment, (5) not chitosan coated (0%) packed with wrapping plastic, (6) 0.5% chitosan concentration packed with wrapping plastic, (7) 1% chitosan concentration packed with wrapping plastic, (8) 2% chitosan concentration is packed with plastic wrapping. The results showed that the coating treatment concentrations of 0.5% chitosan and 1% combined with platinum wrapping packaging treatments stored at low temperatures, were able to provide the best results to extend the shelf life of broccoli.